2015
DOI: 10.1038/srep09198
|View full text |Cite
|
Sign up to set email alerts
|

The juxtamembrane regions of human receptor tyrosine kinases exhibit conserved interaction sites with anionic lipids

Abstract: Receptor tyrosine kinases (RTKs) play a critical role in diverse cellular processes and their activity is regulated by lipids in the surrounding membrane, including PIP2 (phosphatidylinositol-4,5-bisphosphate) in the inner leaflet, and GM3 (monosialodihexosylganglioside) in the outer leaflet. However, the precise details of the interactions at the molecular level remain to be fully characterised. Using a multiscale molecular dynamics simulation approach, we comprehensively characterise anionic lipid interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 74 publications
6
104
0
Order By: Relevance
“…Thus, by way of comparison with experiments, (1) anionic lipids can promote GPCR/G protein interactions, and (2) in the absence of PIP 2 the K d is sub-micromolar, both of which agree with our simulations. Interactions with PIP 2 are known for other membrane signaling proteins, e.g., ion channels (Hansen, 2015), receptor tyrosine kinases (Hedger et al, 2015), and neurotransmitter transporters (Khelashvili et al, 2015). Thus, our studies raise the possibility of PIP 2 -mediated crosstalk between GPCRs and other signaling systems (Fu et al, 2017) in cell membranes.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, by way of comparison with experiments, (1) anionic lipids can promote GPCR/G protein interactions, and (2) in the absence of PIP 2 the K d is sub-micromolar, both of which agree with our simulations. Interactions with PIP 2 are known for other membrane signaling proteins, e.g., ion channels (Hansen, 2015), receptor tyrosine kinases (Hedger et al, 2015), and neurotransmitter transporters (Khelashvili et al, 2015). Thus, our studies raise the possibility of PIP 2 -mediated crosstalk between GPCRs and other signaling systems (Fu et al, 2017) in cell membranes.…”
Section: Discussionmentioning
confidence: 57%
“…Despite these limitations, the approaches discussed have achieved significant success in identifying a range of lipid interaction sites on membrane proteins, controlled and tested against experimental data including mass spectrometry (Gupta et al, 2017;Liko et al, 2016;Yen et al, 2018), crystallographic (Arnarez et al, 2013a;Schmidt et al, 2013;Van Eerden et al, 2017;Zeppelin et al, 2018), NMR spectroscopy Hedger et al, 2016b), and mutational functional data (Hedger et al, 2016a;Hedger et al, 2015;Stansfeld et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Simulation data was analysed using VMD (Humphrey et al, 1996), tools implemented in GROMACS (Hess et al, 2008), and in-house protocols. Protein-lipid contact analysis employed a cutoff distance of 0.6 nm, based on radial distribution functions for CG lipid molecules (Hedger et al, 2015). Likewise, annular lipids were calculated as those within 0.6 nm of the protein surface.…”
Section: Coarse-grained Simulationsmentioning
confidence: 99%
“…In the context of cancer, phosphoinositides were shown to be major regulators of cell motility, invasion, and metastasis [Yamaguchi et al, 2010; Gagliardi et al, 2015; Lien et al, 2017]. Recent studies revealed, several classes of transmembrane receptors and ion channels might be regulated by PIP2, or at least bind this signaling lipid with considerable affinity [Hedger et al, 2015;Kolay et al, 2016, Chadli et al, 2017. Thus, PIP2 signaling may results in a cell-global concerted response to environmental changes.…”
Section: Introductionmentioning
confidence: 99%